Polyporus miscanthi (Polyporaceae, Basidiomycota), a new polypore on Miscanthus (Poaceae) from Guangxi, South China - Zhang, Qiu-Yue; Liu, Hong-Gao; Zeng, Guang-Yu; Dai, Yu-Cheng (Phytotaxa, 2024)
Polyporus is a widespread genus with highly variable morphological features and intricate phylogenetic relationships. Polyporus miscanthi, collected from Guangxi Autonomous Region, South China, is presented as a new species based on both morphological and phylogenetic analyses. It is characterized by annual, solitary, eccentrically stipitate basidiomata with irregularly circular, depressed center or infundibuliform pilei, yellowish to buff pileal surface with radially aligned stripes, white to cream pores, 4–5 per mm, a mouse gray to black stipe, cylindrical basidiospores measuring 9–11 × 3.5–4.5 μm, and growth on rotten Miscanthus. We present the new species with illustrated macro- and micro morphological description and comparison with morphologically similar or phylogenetically related species. Additionally, we provide a key to the known species of Polyporus in China.